Biases in the perception of self-motion during whole-body acceleration and deceleration - Tremblay, Luc; Kennedy, Andrew; Paleressompoulle, Dany; Borel, Lilinane; Mouchnino, Laurence; Blouin, Jean (Frontiers in Integrative Neuroscience, 2013)
Several studies have investigated whether vestibular signals can be processed to determine the magnitude of passive body motions. Many of them required subjects to report their perceived displacements offline, i.e. after being submitted to passive displacements. Here, we used a protocol that allowed us to complement these results by asking subjects to report their introspective estimation of their displacement continuously, i.e. during the ongoing body rotation. To this end, participants rotated the handle of a manipulandum around a vertical axis to indicate their perceived change of angular position in space at the same time as they were passively rotated in the dark. The rotation acceleration (Acc) and deceleration (Dec) lasted either 1.5 s (peak of 60 deg/s2, referred to as being "High") or 3 s (peak of 33 deg/s2, referred to as being "Low"). The participants were rotated either counter-clockwise or clockwise, and all combinations of acceleration and deceleration were tested (i.e., AccLow-DecLow; AccLow-DecHigh; AccHigh-DecLow; AccHigh-DecHigh). The participants' perception of body rotation was assessed by computing the gain, i.e. ratio between the amplitude of the perceived rotations (as measured by the rotating manipulandum’s handle) and the amplitude of the actual chair rotations. The gain was measured at the end of the rotations, and was also computed separately for the acceleration and deceleration phases. Three salient findings resulted from this experiment: i) the gain was much greater during body acceleration than during body deceleration, ii) the gain was greater during High compared to Low accelerations and iii) the gain measured during the deceleration was influenced by the preceding acceleration (i.e., Low or High). These different effects of the angular stimuli on the perception of body motion can be interpreted in relation to the consequences of body acceleration and deceleration on the vestibular system and on higher-order cognitive processes.